Fabricating Ga doped and MgO embedded nanomaterials for sorption-enhanced steam reforming of methanol. Issue 13 (1st March 2022) - Sun, Zhao; Liu, Junpeng; Zhang, Rongjun; Wu, Yu; Li, Hongwei; Toan, Sam; Sun, Zhiqiang
Abstract : Sorption-enhanced steam reforming of methanol (SE-SRM) is a promising approach to creating a high-purity hydrogen supply. Abstract : Sorption-enhanced steam reforming of methanol (SE-SRM) is a promising approach to creating a high-purity hydrogen supply. However, catalysts suffer from activity deactivation and low CO2 uptake capacity. In this study, we investigate the role of Ga doping of Cu–MgO in SE-SRM by synthesizing a series of MgO embedded x GaCuMg catalytic sorbents via a sol–gel method. The TEM-EDX mapping results indicate that MgO nanoparticles can be successfully embedded in the bulk-phase of the catalytic sorbent with a stabilized microstructure. The results from in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) reveal that the Ga-doped catalytic sorbent is conducive to promoting the conversion of C-containing intermediates in SE-SRM, and absorbing CO2 in the form of bidentate carbonate rather than monodentate carbonate. Experimental studies verify that the best uptake capacity of 18GaCuMg catalytic sorbent (36.25 mg CO2 /g MgO) achieves almost complete conversion of methanol (99.70%) with 100% H2 selectivity at 200 °C. Specifically, no CO is formed during the kinetic-control stage of SE-SRM. Density functional theory (DFT) calculations based on the Cu(111)Ga2 O3 (202)MgO(200) model revealed that the Ga doping can enhance the adsorption energies of methanol and carbon dioxide, promoting methanol activation and increasing CO2 uptake capacity. These findings provide valid strategies for functionalized nanomaterial design, which will substantially promote the SE-SRMR performance with desired catalytic sorbent recyclability.